2020
DOI: 10.3390/molecules25030700
|View full text |Cite
|
Sign up to set email alerts
|

The Tomato Metallocarboxypeptidase Inhibitor I, which Interacts with a Heavy Metal-Associated Isoprenylated Protein, Is Implicated in Plant Response to Cadmium

Abstract: Metallocarboxypeptidases are metal-dependent enzymes, whose biological activity is regulated by inhibitors directed on the metal-containing active site. Some metallocarboxypeptidase inhibitors are induced under stress conditions and have a role in defense against pests. This paper is aimed at investigating the response of the tomato metallocarboxypeptidase inhibitor (TCMP)-1 to Cd and other abiotic stresses. To this aim, the tomato TCMP-1 was ectopically expressed in the model species Arabidopsis thaliana, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…This protein family was recently discovered in vascular plants and its members are characterized by two domains: one or more heavy metal associated domain(s) (HMA) and one C-terminal isoprenylation motif [ 6 , 16 ]. The presence of the HMA domain(s) implies a function in either the heavy metal detoxification or the maintenance of heavy metal homeostasis [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Recent studies found a connection between the HIPPs and the stress responses of plants, establishing a more complex function of this protein family [ 6 , 8 , 10 , 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…This protein family was recently discovered in vascular plants and its members are characterized by two domains: one or more heavy metal associated domain(s) (HMA) and one C-terminal isoprenylation motif [ 6 , 16 ]. The presence of the HMA domain(s) implies a function in either the heavy metal detoxification or the maintenance of heavy metal homeostasis [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Recent studies found a connection between the HIPPs and the stress responses of plants, establishing a more complex function of this protein family [ 6 , 8 , 10 , 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…This stress alleviation was also related to Zn transporters and chelating ligands. For example, the ABC transporters (43.4%), HIPP (22.5%), and DTX (14.5%) have been previously reported to be related to the alleviation of Zn and Cd stress ( Moons, 2003 ; Dong et al, 2019 ; Manara et al, 2020 ), with ABC transporters playing a role in the compartmentalization of excess metals in vacuoles ( Sharma et al, 2016 ). Furthermore, of the eight groups of chelating ligands, heat shock protein (23.7%) is also related to metal stress alleviation ( Hasan et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, metallocarboxypeptidase inhibitor in Solanum lycopersicum (TCMP‐1) and Solanum tuberosum (StPCI) was induced in the leaves by wounding, elicitors of biotic stress and abiotic stress of salinity and Cd toxicity, while the TCMP‐1 was further demonstrated to interact with a tomato heavy metal‐associated isoprenylated plant protein (HIPP)26 (Villanueva et al 1998, Manara et al 2020). Phylogenetic analysis revealed that the metallocarboxypeptidase inhibitors of tobacco (NtMCPIa and NtMCPIb) are more closely related to that of Solanum lycopersicum (SlTCMP‐1) and Solanum tuberosum (StPCI) (Manara et al 2020). The involvement of these proteins, along with other mechanisms in the detoxification of heavy metal stress in Solanaceae trichomes is represented in Fig.…”
Section: Trichomes In Heavy Metal Resistance Of Solanaceaementioning
confidence: 99%